Sequência de ensino-aprendizagem no processo de formação continuada : contribuições e reflexões de professores em exercício - Menezes, Alexandre Mota (2016)
On the quest for improvement of science teaching, both discussions and reflexions in beginning and continuous formation of teachers show to be fundamental. So, this study aims to present subjects for discussion came from a research project on epistemological, pedagogical, and didactic influences in choices made by teachers insert in a continuous formation process, working with a validation named “Sequência de ensino-aprendizagem – SEA” (Teaching-learning sequence). The relative material was developed by this researcher, and it was validated during graduation course. In postgraduate course, the so-called SEA was analyzed, put in, and remade by teachers of high-school, aiming the comprehension of the choices made by teachers during program. Discussions have shown that difficulties faced by the teachers, as well as the need to apply all subject of a systematic way, the teacher-student relationship, organizational and structural questions of school have been determinant factors in choices made by teachers in their activities. Such difficulties interfere in application of materials with the so-called “Abordagem CTS” (Scientific, technological and social approach), and “Experimentação problematizadora”.